Psychological Condition Reflected in Adam Haslett's Short Story You Are Not Stranger Here (2002) - Geovani, Oliffia Larensza; Al-Hafizh, Muhd. (English Language and Literature, 2024)
This study aimed to discus the psychological problem condition in Short story You’re Not Stranger Here by Adam Haslett (2002). This analysis  elaborated about the psychological problem (trauma) and the negative impact of the psychological problem itself. This analysis described about “Psychological Condition Reflected in Adam Haslett’s You’re Not Stranger Here  (2002). This research conducted using the descriptive qualitative approach. This data analysis was to analyze novel You’re Not Stranger Here (2002) by Adam Haslett. The data was collected from the quotation in the novel. The data was in the form of sentences, words and phrases .The source of data in this research was a novel written by Adam Haslett entitled You Are Not Stranger Here. The result of analysis "You Are Not a Stranger Here" by Adam Haslett delves deeply into the complexities of human psychology and mental illness through interconnected short stories. It portrays a range of psychological problems, including depression, anxiety, and trauma, and highlights their profound impact on individuals' lives. Through the characters' experiences, the short story sheds light on the various ways in which these conditions manifest, intertwine, and challenge their ability to function in their daily lives.